Morphological transformation of numerical phrases into verbs in the Javanese language - Somawati, Ni Putu; Wajdi, Majid; Susanto, Budi; Udoudom, Uduak Imoh; Claridad, NF; Mohammed, LA (Yayasan Mitra Persada Nusantara, 2024)
This study explores the morphological process in the Javanese language where numerical phrases are transformed into verbs through the addition of the prefix